Social Media Marketing, Product Quality, and Price on Farhan Collection Customer Satisfaction - Setiawan, I Made Tedi; Putri, Sukmasari Triana Gita; Putra, I Ketut Johny Pramanda (PT Keberlanjutan Strategis Indonesia, 2026)
Over the last two years, Farhan Collection has experienced fluctuations in its sales revenue; consequently, this study was conducted to analyze the influence of product quality, pricing, and social media marketing on customer satisfaction. This quantitative research involved 97 respondents selected via purposive sampling, determined by the Slovin formula with a 10% margin of error. Data were gathered through a 5-point Likert scale questionnaire then analyzed with multiple linear regression. The findings confirm that customer satisfaction is collectively influenced by significant social media marketing effectiveness, maintained product quality, and appropriate pricing, with an Adjusted R-Square value of 0.680. Furthermore, partial testing indicates that all three variables serve as strong predictors of customer satisfaction. Based on these results, Farhan Collection is advised to consistently integrate high product standards with strategic digital promotion to sustain customer satisfaction